2018
DOI: 10.1111/opo.12444
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in a community optometrist led cataract shared care scheme

Abstract: Direct cataract referrals from accredited community optometrists led to a majority of patients receiving a definitive clinical decision during first consultation. Postoperative community follow up reduced hospital visits and allowed for convenient consultation closer to home following uncomplicated cataract surgery. A service-level agreement with an accreditation scheme measured against KPIs enhances the accountability of stakeholders involved in the cataract shared care scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These direct pathways have been introduced to ensure that the ‘Action on Cataracts’ guidelines were followed, and that patients referred for cataract surgery were only seen within the HES when they had reduced measured vision, were symptomatic and expressed a willingness for surgery. Two early 47 , 49 and one more recent study 36 reported that surgery listing rates were significantly higher (83%–87%) when compared to conventional referral pathways (63%–78%).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These direct pathways have been introduced to ensure that the ‘Action on Cataracts’ guidelines were followed, and that patients referred for cataract surgery were only seen within the HES when they had reduced measured vision, were symptomatic and expressed a willingness for surgery. Two early 47 , 49 and one more recent study 36 reported that surgery listing rates were significantly higher (83%–87%) when compared to conventional referral pathways (63%–78%).…”
Section: Resultsmentioning
confidence: 98%
“…El-Abiary et al, 2021 23 Muttuvelu et al, 2021 8 Wang et al, 2021 50 Kern et al, 2020 7 Phu et al, 2020 34 Konstantakopoulou et al, 2018 37 Kortuem et al, 2018 66 Ford et al, 2019 51 Forbes et al, 2017 25 Kotecha et al, 2017 70 Mason et al, 2017 28 Ly et al, 2017 38 Balaskas et al, 2016 65 Ly et al, 2016 39 El-Assal et al, 2015 41 Keenan et al, 2015 43 Ratnarajan et al, 2015 44 Roberts et al, 2015 42 Goudie et al, 2014 59 Ratnarajan et al, 2013a 6 Ratnarajan et al, 2013b 45 Trikha et al, 2012 62 Devarajan et al, 2011 54 Parkins et al, 2011 55 Ang et al, 2009 48 Park et al, 2009 47 Hanson et al, 2008 61 Patel et al, 2006 64 Hind et al 2022 68 Huang et al, 2020 33 Gunn et al, 2019 35 Bowes et al, 2018 36 McAlinden et al, 2016 40 Borooah et al, 2013 60 Kelly et al, 2011 63 Bourne et al, 2010 46 Cameron et al, 2009 4 Lash et al, 2006 49 Retrospective and Prospective (n=3)…”
Section: Retrospective (N=29)mentioning
confidence: 99%
“…57 We found examples of vertical integration strategies to mitigate this, including shared-care between optometrists and ophthalmologists in the UK for people with glaucoma 24 and cataract. 59 A common theme of studies reporting elements of service integration was the importance of good communication between providers and enabling technology-including teleophthalmology and secure electronic health information systems-to enhance efficiency and timeliness of the service. 57 Refractive error correction is a condition that highlights the importance of integrated eye care services.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure appropriate use of time and resources schemes have been set up for additional optometrist training to perform cataract pre-assessments. Bowes et al created an annual accreditation course for Cambridgeshire optometrists in an effort to improve the quality of referrals to ophthalmology [ 9 ]. And Gaskell et al [ 4 ] developed a specialist educational course to accredit optometrists in the assessment of cataract.…”
Section: Discussionmentioning
confidence: 99%